Analisis Keterampilan Public Speaking Guru Kelas V dalam Melaksanakan Pembelajaran di SDN 261 Bilamporoa Kecamatan Bontotiro Kabupaten Bulukumba - Ayu Rahmawati Sam; Agus; Abd. Rajab (PT PUSTAKA CENDEKIA GROUP, 2024)
Teachers are a bridge of knowledge for students at school. Therefore, teachers need good skills to transmit knowledge to students at school, because in transferring knowledge to students they must use the best methods so that learning objectives can be achieved as they should. What usually happens in schools is that the teacher's role in the class is more dominant than the students, even though students are also expected to play an active role in the class, being able to convey their ideas and ideas by speaking boldly. However, students will not be able to express their ideas or speak if the teacher does not provide examples and opportunities to speak as well. Therefore, teachers are expected to be able to master the class by speaking fluently and attracting student feedback by using Public Speaking skills so that a good teaching and learning process can occur.